Physico-chemical characteristics of pectin from mango peels - Alotaibi, Abeer; Jaswir, Irwandi; Jamal, Parveen (2010)
With the increase in production of processed fruit products, the amount of fruit wastes generated is increasing enormously. Large amount of these wastes poses the problem of disposal without causing environmental pollution. A valuable byproduct that can be obtained from fruit wastes is pectin. Pectin designates those water soluble pectinic acid (colloidal polygalacturonic acids) of varying methyl ester content and degree of neutralization, which are capable of forming gels with sugar, and acids, under suitable condition. This study was conducted to determine physico-chemical characteristics of pectin derived from mango peels, a popular fruit in Malaysia, using acid extraction. Physico-chemical properties evaluated were ash, moisture, galacturonic acid analysis, viscosity, DE and color. A central composite design was used to optimize the condition of three independent factors affecting the extraction process, i.e A: extraction temperature (*C); B: pH of the mixture; and C: time of extraction (h). Results showed that the use of 1N citric acid was found to be suitable for the extraction of the pectin from mango peels, with acceptable physico-chemical characteristics, while the extraction at 90*C and pH 2.75 for 2.5 was identified as the best condition for production of crude pectin from mango peels.